New literature of China - Мaдиев Д. A.; Шәріпқaзы Н. (Journal of Oriental Studies, 2017)
In the article examined large changes in the field of literature of China ХХ centuries, in the period of becoming of New literature of China. Separately studied development of literary genres as poetry, prose, dramaturgy, work of well-known poets and writers of that time is analysed. A contribution is examined to becoming of new literature of such writers of contemporaneity as Lu Xun, Guo Moruo, Mao Dun, and also writers of late generation to Wan Мeng, Мо Yan, that came in literature under influence of “Motion of 4 Mays”, and began to propagandize works of realistic direction.